2022
DOI: 10.1155/2022/6204880
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Coronavirus Disease (COVID-19) on Human Semen: No Evidence of Coronavirus in Semen of Patients

Abstract: Background. In December 2019, a severe acute respiratory syndrome (SARS-COV-2) was found in China. The coronavirus can impact different organs, as shown by the virus having been detected in urine, blood, oropharyngeal, and feces. This study was done to assess the impact of COVID-19 on semen analysis and to evaluate the existence of the virus in the semen of infected men. Methodology. Forty fertile men with COVID-19 were confirmed by an oropharyngeal sample. The men were divided into two groups. The semen of tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…In addition, Pazir et al [27] reported that there were no significant differences in semen parameters before and after COVID-19 in terms of semen volume, sperm concentration, and progressive motility. Likewise, in a recent study by Vahidi et al [30], the semen analyses between patients in the acute and clinical recovery stages showed no significant differences between the two groups in semen count or motility parameters. Additionally, in their retrospective study, Wang et al [31] studied the semen parameters for male partners in couples undergoing in vitro fertilization cycles in a hospital in Wuhan, China, between May 2020 and February 2021.…”
Section: Discussionmentioning
confidence: 73%
“…In addition, Pazir et al [27] reported that there were no significant differences in semen parameters before and after COVID-19 in terms of semen volume, sperm concentration, and progressive motility. Likewise, in a recent study by Vahidi et al [30], the semen analyses between patients in the acute and clinical recovery stages showed no significant differences between the two groups in semen count or motility parameters. Additionally, in their retrospective study, Wang et al [31] studied the semen parameters for male partners in couples undergoing in vitro fertilization cycles in a hospital in Wuhan, China, between May 2020 and February 2021.…”
Section: Discussionmentioning
confidence: 73%
“…Li et al (2020a) tried to answer this question using RT-PCR assay to detect SARS-CoV-2 in semen. Semen testing showed that 6/38 patients (15.8%) had positive results for SARS-CoV-2, including 4/15 patients (26.7%) who were in the acute stage of infection and 2/23 patients (8.7%) who were Twelve other studies (Holtmann et al 2020;Best et al 2021;Burke et al 2021;Gupta et al 2021;Guo et al 2021a;Ma et al 2021;Ruan et al 2021;Scroppo et al 2021;Temiz et al 2021;Dipankar et al 2022;Donders et al 2022;Vahidi et al 2022) could not detect SARS-CoV-2 virus in semen samples. For example, Ma et al (2021) used qRT-PCR to detect the SARS-CoV-2 virus in semen samples receiving negative results for all 12 male study participants.…”
Section: Resultsmentioning
confidence: 86%
“…There was no RNA detected in any participant's semen. Twenty men in the acute stage and 20 men in the clinical recovery stage were examined and all tested SARS-CoV-2 negative (Vahidi et al 2022). Some (Scroppo et al 2021) divided their study participants into two groups (mild and moderate COVID-19 disease), where SARS-CoV-2 had not been detected in any semen samples, while others (Holtmann et al 2020) did not detect SARS-CoV-2 RNA in semen samples from either recovered (n = 18) or acute infected (n = 2) subjects in the investigated time after the end of symptoms of 32.7 days on average using RT-PCR.…”
Section: Exclusion: Men With Other Acutementioning
confidence: 99%
See 1 more Smart Citation
“…The presence of the virus in the male reproductive tissue of two men with erectile dysfunction (ED) and other infected patients has been confirmed in past studies (Kresch et al, 2021;Vahidi et al, 2022). As the testis is one of the organs with high levels of constitutive expression of ACE2, the virus could directly damage testicular tissues (Chen et al, 2020;Wang & Xu, 2020).…”
Section: Introductionmentioning
confidence: 85%